Are You My Stranger? Developing a Biblical Pedagogy of Migration in Syriac Christian Sources - Doerfler, Maria E. (2024)
Migration, in late antiquity as in the present century, was a widespread phenomenon that came at great cost to individuals, families, and communities. The need to care for the “strangers” in their midst accordingly became an active, vibrant concern for Christian leaders already during the first centuries of the Common Era. This is particularly true for Syriac communities, where the commemoration of those who had died far from their homes traces itself at least to the fifth century. To encourage congregations’ support of and identification with migrants, homilists and hymnodists drew on biblical models, reading the patriarchs of the Hebrew Scriptures and the towering figures of the New Testament through the lens of migration and exile. This article focuses on some of the most prominent examples of these practices, including Jacob, Moses, and Jesus, to examine the pedagogical concerns and strategies that emerge from the migrant-centric writings of early Syriac literature.
Keywords: Syriac Christianity; Ritual; Moses; Migration; Liturgy; Jacob